Hauntology: A tale of two cities - Lawrence, Salmah Eva-Lina (The Australian journal of anthropology, 2025)
Triggered by the 50th anniversary of Papua New Guinea's independence, this paper is a personal reflection on growing up in the city of Port Moresby in the mid-1960s through to the early 1980s in contrast to the city it is in 2025.